Tide and movements: When accumulation of territorial conflicts achieves limited political results. The case of Chiloé, Chile - Delamaza Escobar, Gonzalo Antonio (2023)
The literature on socio-territorial conflicts and social movements has focused on «accumulative» and «joint» effects. The case of the Chiloé archipelago shows a process of diachronic accumulation since the beginning of the 21st century. That accumulation is combined with external factors associated with the salmon industry cycle, the dominant productive activity, and the political and institutional process. Theoretically, the case might res-pond to transformative consequences since the territorial accumulation here is not different from what happened in similar territorial conflicts. However, this paper proposes that contextual factors –such as the political alliances and the state and private support of the salmon industry– limit both the articulation of diverse actors and the scope of socio-political transformations to address the conflicts’ roots. In this regard, the paper concludes that the political consequences tend to be limited or circumscribed to minor changes while also offering new theoretical elements to enrich the original model of political consequences.